Mr. and Mrs. Madison's war America's first couple and the second war of independence - Howard, Hugh (Bloomsbury Press, 2012)
The War of 1812 remains the least understood of America's wars. To some it was a conflict that resolved nothing, but to others, it was our second war of independence, settling once and for all that America would never again submit to Britain. At its center was James Madison--our most meditative of presidents, yet the first one to declare war. And at his side was the extraordinary Dolley, who defined the role of First Lady, and who would prove perhaps her husband's most indispensable ally. Here, drawing on countless primary sources, acclaimed historian Hugh Howard presents an account of the conflict as James and Dolley Madison experienced it, and rediscovers a conflict fought on land and sea--from the shores of the Potomac to the Great Lakes--that proved to be a critical turning point in American history.--From publisher description